El Desarrollo Histológico del Tejido Óseo en carencia de Riboflavina - Delgadillo Ávila, Juana Rosa (2003)
The investigation aim is determining the histological changes which appear in the femur and the jaw of the albino rats offspring during the gestation and the nursing, until the 28 days of age having different riboflavin concentrations in the diet. It was conformed four groups of Holtzman albinos rats with reproductions capacity, according to the demand of riboflavin: Group A (100% of B), Group B (50% of B), Group C (25% of B) and Group D (0% of B). The rats offspring of each group were extracted and sacrifidied at the 0, 7,14, 21 and 28 days from the birth. Then they were submitted a histological studying with Eosin Hematoxylin and Masson Stains. The deficiency or total lack of B2 produced alterations in the of offspring growth and development. The obtained results showed: small light and diminution of the corporal weight, and microscopically reveals: for total lack of Riboflavin in the diet (0%), presented reduction on the cellular populations of osteocytes, osteoblastes and osteoclasses and a scare quantify of collagen fibers. That difference is more notorious from the 7 days of age.